Big Data in psychological research - Woo, Sang Eun (American Psychological Association, 2020)
Big Data in Psychological Research provides an overview of big data theory, research design and analysis, collection methods, applications, ethical concerns, best practices, and future research directions for psychologists
Keywords: Psychologie; Big Data; Konferenzschrift -- 17.05.2018-19.05.2018 -- West Lafayette, USA; Aufsatzsammlung